Structure and evolution of photosystem I in the early-branching cyanobacterium Anthocerotibacter panamensis - Han-Wei Jiang; Christopher J. Gisriel; Tanai Cardona; David A. Flesher; Gary W. Brudvig; Ming-Yang Ho (Proceedings of the National Academy of Sciences, 2025)
Thylakoid-free cyanobacteria are thought to preserve ancestral traits of early-evolving organisms capable of oxygenic photosynthesis. However, and until recently, photosynthesis studies in thylakoid-free cyanobacteria were only possible in the model strain Gloeobacter violaceus , limiting our understanding of photosynthesis evolution. Here, we report the isolation, biochemical characterization, cryo-EM structure, and phylogenetic analysis of photosystem I (PSI) from a recently discovered thylakoid-free cyanobacterium, Anthocerotibacter panamensis , a distant relative of the genus Gloeobacter . We find that A. panamensis PSI exhibits a distinct carotenoid composition and has one conserved low-energy chlorophyll site, which was lost in G. violaceus . Furthermore, PSI in thylakoid-free cyanobacteria has changed at the sequence level to a degree comparable to that of other strains, yet its subunit composition and oligomeric form might be identical to that of the most recent common ancestor of cyanobacteria. This study therefore provides a glimpse into the ancient evolution of photosynthesis.